Adaptive Immunity in Pulmonary Sarcoidosis and Chronic Beryllium Disease - Greaves, Sarah A.; Atif, Shaikh M.; Fontenot, Andrew P. (Frontiers in Immunology, 2020)
Pulmonary sarcoidosis and chronic beryllium disease (CBD) are inflammatory granulomatous lung diseases defined by the presence of noncaseating granulomas in the lung. CBD results from beryllium exposure in the workplace, while the cause of sarcoidosis remains unknown. CBD and sarcoidosis are both immune-mediated diseases that involve Th1-polarized inflammation in the lung. Beryllium exposure induces trafficking of dendritic cells to the lung in a mechanism dependent on MyD88 and IL-1α. B cells are also recruited to the lung in a MyD88 dependent manner after beryllium exposure in order to protect the lung from beryllium-induced injury. Similar to most immune-mediated diseases, disease susceptibility in CBD and sarcoidosis is driven by the expression of certain MHCII molecules, primarily HLA-DPB1 in CBD and several HLA-DRB1 alleles in sarcoidosis. One of the defining features of both CBD and sarcoidosis is an infiltration of activated CD4+ T cells in the lung. CD4+ T cells in the bronchoalveolar lavage (BAL) of CBD and sarcoidosis patients are highly Th1 polarized, and there is a significant increase in inflammatory Th1 cytokines present in the BAL fluid. In sarcoidosis, there is also a significant population of Th17 cells in the lungs that is not present in CBD. Due to persistent antigen exposure and chronic inflammation in the lung, these activated CD4+ T cells often display either an exhausted or anergic phenotype. Evidence suggests that these T cells are responding to common antigens in the lung. In CBD there is an expansion of beryllium-responsive TRBV5.1+ TCRs expressed on pathogenic CD4+ T cells derived from the BAL of CBD patients that react with endogenous human peptides derived from the plexin A protein. In an acute form of sarcoidosis, there are expansions of specific TRAV12-1/TRBV2 T cell receptors expressed on BAL CD4+ T cells, indicating that these T cells are trafficking to and expanding in the lung in response to common antigens. The specificity of these pathogenic CD4+T cells in sarcoidosis are currently unknown.